Allocentric Spatial Memory Testing Predicts Conversion from Mild Cognitive Impairment to Dementia: An Initial Proof-of-Concept Study - Wood, Ruth A.; Moodley, Kuven K.; Lever, Colin; Minati, Ludovico; Chan, Dennis (Frontiers in Neurology, 2016)
The hippocampus is one of the first regions to exhibit neurodegeneration in Alzheimer’s disease (AD) and knowledge of its role in allocentric spatial memory may therefore aid early diagnosis of AD. The 4 Mountains Test (4MT) is a short and easily administered test of spatial memory based on the cognitive map theory of hippocampal function as derived from rodent single cell and behavioral studies. The 4MT has been shown in previous cross-sectional studies to be sensitive and specific for mild cognitive impairment due to AD. This report describes the initial results of a longitudinal study testing the hypothesis that allocentric spatial memory is predictive of conversion from mild cognitive impairment to dementia. Fifteen patients with mild cognitive impairment underwent baseline testing on the 4MT in addition to CSF amyloid/tau biomarker studies, volumetric MRI and neuropsychological assessment including the Rey Auditory Verbal Learning Test (RAVLT) and Trail Making Test “B” (TMT-B). At 24 months, 9/15 patients had converted to AD dementia. The 4MT predicted conversion to AD with 93% accuracy (Cohen’s d = 2.52). The predictive accuracies of the comparator measures were as follows: CSF tau/β-amyloid1-42 ratio 92% (d = 1.81), RAVLT 64% (d = 0.41), TMT-B 78% (d = 1.56), and hippocampal volume 77% (d = 0.65). CSF tau levels were strongly negative correlated with 4MT scores (r = -0.71). This proof-of-concept study provides initial support for the hypothesis that allocentric spatial memory testing is a predictive cognitive marker of hippocampal neurodegeneration in pre-dementia AD. The 4MT is a brief, noninvasive, straightforward spatial memory test and is therefore ideally suited for use in routine clinical diagnostic practice. This is of particular importance given the current unmet need for simple accurate diagnostic tests for early AD and the ongoing development of potential disease-modifying therapeutic agents which may be more efficacious when given earlier in the disease course. By applying a test based on studies of hippocampal function in rodents to patient populations this work represents the first step in the development of translatable biomarkers of hippocampal involvement in early AD for use in both animal models and human subjects.